SIFAT FISIS KAYU BERKUALITAS RENDAH DARI RIAU SETELAH MELALUI PROSES PENGAWETAN POHON DENGAN TEKNIK BANDAGE DAN INFUS - Sribudiani, Evi; Somadona, Sonia; Sulaeman, Rudianda; Syafrinal, Syafrinal; Yusuf, Sulaeman; Amin, Yusup; Tarmadi, Didi; Pramasari, Dwi Ajias; Damayanti, Ratih; Djarwanto, Djarwanto (Wahana Forestra: Jurnal Kehutanan, 2019)
The potential of high-quality wood for various purposes over the past decade is very difficult to obtain. This is due to the high rate of doforestation and forest degradation, especially in Riau Province. Examples of the use of high-quality wood, especially in Riau Province, is as material for creating 'pathways' in the context of preserving track culture in the Kuantan Singingi Regency. The purpose of this study is to determine the physical properties of red balam wood and bintangur that grow in Riau before and after the preservation process, and determine the strength class of red balam wood and bintangur that grows in Riau. The research was carried out on the starur trees and red balam with a diameter of 34-38 cm, tree height 18-22 m. The tree sample comes from the Rumbio customary forest and the Minas Tahura KPHP Riau Province. Examination of physical properties using British standards in 1957. The results showed that based on specific gravity, the red balam wood and bintangur before preserved and included as strong class II. The average moisture content of each wood is 14-30%. The largest wood shrinkage development in each wood occurs at the base of the wood.